Analysis of the Effect of the Implementation of the Quantum Teaching Method on Accounting Learning in Class XI IPS SMA N 1 Laguboti - Sibarani, Blasius Erik (Pandawan, 2021)
The learning method is one key to the success of KBM and the key achievement of learning goals. The learning method is a method used to implement the plan that has been prepared in the form of real and practical activities to achieve the learning objectives, which is a way chosen by educators to optimize the learning process that aims to achieve the expected learning goals. A classroom lessons will take place smoothly if the learning design with interesting learning methods and improve the enthusiastic students to receive lessons. Nowadays a lot of teaching in the classroom makes the students bored and lazy due to running with monotonous so KBM just go away without achieving the purpose of learning. Therefore, learning must be designed such accounting and attractive as possible so that students can be serious in accepting the lessons so that learning does not take place freely. This study aims to obtain a picture of how the effect of the application of the method quantum teaching the process of teaching in the classroom and to determine the effectiveness of the use of this method in accounting subjects. Data collection techniques in this research is by distributing questionnaires, participant observation, field notes. Data analysis techniques in this research is quantitative descriptive data analysis. The results showed that there are significant application of the method quantum teaching the process of teaching and there is effective use of the method quantum teaching the accounting subjects.